Intellectual Property Rights Protection in the Digital Economy - Muhamad Agung Dharmajaya (SEAN Institute, 2024)
The rapid development of information technology has transformed the global business landscape into the digital economy era. However, this phenomenon has also brought massive threats to the protection of Intellectual Property Rights (IPR) through various new modes of cyber violations. This study aims to analyze the effectiveness of positive legal regulations in protecting IPR in the digital ecosystem and identify multidimensional obstacles to its enforcement. The research method used is normative juridical with a statutory and conceptual approach through qualitative secondary data analysis. The results indicate that current positive legal regulations are ineffective due to the rigid nature of conventional law and the lag behind the rapid pace of digital technological innovation, thus creating a legal vacuum (rechtvacuum), especially in regulating the generative Artificial Intelligence (AI) ecosystem and the responsibility of digital platforms. Law enforcement in cyberspace is also hampered by structural barriers in the form of cross-border jurisdictional conflicts, technical barriers in the form of manipulation of electronic evidence and the anonymity of perpetrators, and cultural barriers in the form of low public legal awareness that is permissive towards digital piracy. This study concludes that regulatory reforms are needed that adhere to technology-neutral legislation, integrated with cutting-edge technological solutions such as blockchain and smart contracts to automate copyright and royalty tracking, and supported by strengthened international legal diplomacy and digital literacy education to create a safe digital economy ecosystem for innovators